HUBUNGAN PERSEPSI SISWA TENTANG KOMPETENSI PEDAGOGIK GURU TERHADAP MOTIVASI BELAJAR GEOGRAFI SISWA KELAS X IPS DI MAN 2 KOTA PADANG - Ningsih, Afvi Santrisca; Anwar, Syafri (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
AbstractThis study aims to determine the extent of the relationship between students' perceptions of teacher pedagogic competence towards geography learning motivation of class X IPS students at MAN 2 Padang City. This type of research is included in the correlational quantitative research. The population in this study were students of class X IPS in the 2021/2022 academic year, totaling 174 students. The sampling technique used was proportional random sampling with a proportion of 10% and a sample of 106 students was obtained. Data analysis used a Likert scale using the SPSS version 16.0 program. The technique used is correlation and simple linear regression. The results of the study concluded that there was a relationship between students' perceptions of teacher pedagogic competence having a positive and significant relationship to students' motivation to learn geography. This is evidenced by the correlation coefficient (r) of 0.514, the coefficient of determination (r2) of 26.4%, the value of tcount (6.115) > ttable (1.986) and the value of the regression equation Y = 31,707 + 0.607X which indicates that every time there is an addition one unit on the student's perception variable about the teacher's pedagogic competence, it will increase the score on the student's geography learning motivation variable by 0.607. Keywords: Student perceptions, pedagogic competence, learning motivation